Systems Innovation - Discussion Paper - Mulgan, Geoff; Leadbeater, Charlie (NESTA, 2013)
Introduction Over the past few years there has been growing interest i n systemic innovation. We are defining this as an interconnected set o f innovations, where each influences the other, with innovation both i n the parts of the system and in the ways in which they interconnect. Yet rather than simply theorising, we want to make this practical. We want to explore the potential of systemic innovation to help tackle so me of the key challenges the UK currently faces, from supporting an ag eing population to tackling unemployment. We would also like to open u p the discussion, to engage with the wide and diverse range of experts already working this space to help sharpen up thinking about systemic innovation and influence practical work to advance it. About this pap er The two essays contained within this paper are intended to contribu te to this debate. The first paper by Geoff Mulgan addresses a number of questions about systemic – or ‘joined–up’ – innovation, asking what it means to truly transform a system, encompassing the means, methods , and actions needed to realise its potential. The second paper from C harlie Leadbeater argues that companies, governments, cities, and enti re societies need to move from seeing innovation in products and servi ces as a source of competitive advantage, to focussing on innovation w ith entire systems. Our next steps: helping make systemic innovation u seful and useable This report is just the start. We want to work with academics, practitioners, policymakers, and others in the field, to he lp realise the great potential of connecting and joining up innovative products, services and processes so that the whole is more than the p arts. Over the coming months we will be building upon the rich and div erse literature available (we have start collating this as an annex to this paper), as well as practitioner experience, to ensure we underst and systems more rigorously, as well as the skills, capabilities, meth ods and means needed to help them change for the better.